Analysis of the effectiveness of technical-tactical elements during the serve-receive phase in youth female table tennis athletes - Nikolakakis, A.; Mavridis, G.; Gourgoulis, V.; Katsikadelis, M. (International Journal of Racket Sports Science, 2021)
The aim of the current study was to record and compare the technical and tactical elements of the strokes during serve, receive and winning shots between winning and defeated female table tennis athletes, belonging to the cadet leagues and to study their relation with the outcome of the match. The sample for this study was 36 official table tennis matches (2487 rallies) of cadets (14 ± 1.48 years). The technical and tactical analyses was concerned with the type and direction of the serve and receiving the ball, the success rates of the player serving and receiving, as well as the process of winning a point after an offensive shot. In order to record and analyze the matches, the method of video analysis was used and for the statistical treatment of the data the non-parametric X2 test was implemented. The results revealed that the forehand grip was mainly used for the execution of a serve and the serve of the young female winners was statistically superior to the losers, regarding the score and the rates of successfully receiving the ball. Statistically significant differences were also observed in the first return of the ball after the execution of the serve, where the winners preferred mostly the forehand-push, backhand-topspin and forehand-topspin, making even more winning shots compared to the losers. The findings of the current study could be used by coaches in Cadet Leagues to improve training methods and help them to provide feedback to the athletes during the matches.